2009
DOI: 10.1179/cmq.2009.48.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Precipitate Volume Fraction Estimation in High Strength Microalloyed Steels

Abstract: Many attempts have been made in the past to estimate the volume fraction of small precipitates in steels, both theoretically and experimentally. Theoretical analysis can be very complicated, while experimental analysis can be either difficult or can yield numbers that are inaccurate. In this paper, a simple method is presented to estimate the precipitate volume fraction of nanosize microalloy carbides. The method is based on a combination of simple and well-established thermodynamic calculations for high-tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In particular, the results shown in Fig. 13c are very similar to the size distribution reported for fine Nb-Mo rich precipitates (essentially carbides) that start to form between 950 and 1050 • C in a X100 steel [41]. On the other hand, the constant value of mean particle size measured throughout hot rolling is in agreement with previous works [30] that found that the precipitate size can strongly decrease during hot rolling when long interpass times that allow particle coarsening at high temperatures are used, but mean size is roughly constant throughout rolling if a short interpass time as those used in present work is applied.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…In particular, the results shown in Fig. 13c are very similar to the size distribution reported for fine Nb-Mo rich precipitates (essentially carbides) that start to form between 950 and 1050 • C in a X100 steel [41]. On the other hand, the constant value of mean particle size measured throughout hot rolling is in agreement with previous works [30] that found that the precipitate size can strongly decrease during hot rolling when long interpass times that allow particle coarsening at high temperatures are used, but mean size is roughly constant throughout rolling if a short interpass time as those used in present work is applied.…”
Section: Resultssupporting
confidence: 83%
“…the existence of two distinct populations of precipitates: coarser cuboidal carbonitrides rich in TiN that form above 1150 • C and finer and more spherical NbC-based precipitates that form between 1100 • C and 900 • C [73,80], even though they measured a coarser mean particle size than in this work. On the other hand, previous studies on X100 steels describe fine precipitates having average sizes near 4-5 nm with a remarkable presence of Mo together with smaller amounts of other microalloying elements substituting Nb [33,41]. In particular, the results shown in Fig.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…It should also be noted that the effectiveness of the second-phase trapping approach is highly dependent on the service environment of a material. Due to the constraint of H trapping/storage content arising from the typically low second-phase volume fraction (e.g., below 1% for strengthening carbides in ferritic steels 872 ), such approach is expected to be most effective for the cases with only a limited H uptake from environments (e.g., during the pickling process). However, it should not be an ideal approach for materials operated in H-abundant atmosphere (e.g., H transport and storage) where continuous H ingress will occur and inevitably will saturate the H traps.…”
Section: Comparison Of He Resistance Among Different Materials Systemsmentioning
confidence: 99%
“…In addition to the characteristics of the matrix phase, the effectiveness of the second‐phase trapping approach is also closely linked to the service environment of a material, particularly to the amount of H that enters into a material. Typically, the volume fraction of introduced precipitates in strong and ductile materials is quite low (e.g., below 1% in ferritic steels 102 ). This suggests a limited H storage volume caused by the trapping effect.…”
Section: Microstructure Design Strategies To Mitigate H Embrittlement...mentioning
confidence: 99%